The harmonisation of international trade laws in Africa, with reference to the European Example - Rossouw, Mandi (Department of Commercial Law, 2026)
The issue of legal harmonisation is important for the Africa continent in the light of the current fragmentation of legal systems and the need to realise of the idea of African Unity and the African Economic Community. A key issue in Africa's economic integration will be overcoming the challenges posed by differences in legal traditions and laws. Differences in national laws will become more significant as economic integration progresses and cross-border transactions (international trade) increase. The harmonisation of laws is an important part of the legal infrastructure of integrated economies, and will be a key component of Africa's economic integration process.